A novel strategy for microbial conversion of dairy wastewater into biofertilizer. (15th April 2021) - Gogoi, Mandakini; Biswas, Tethi; Biswal, Prasandeep; Saha, Tuhin; Modak, Ajoy; Gantayet, Lalit Mohan; Nath, Rajib; Mukherjee, Indranil; Thakur, Ashoke Ranjan; Sudarshan, Mathumal; Ray Chaudhuri, Shaon
Abstract: Dairy industry generates copious amount of wastewater from its milk processing unit (1–10 m 3 of wastewater per m 3 of processed milk) which needs to be treated before getting discharged. The conventional treatment processes are tedious, energy intensive, and an additional burden for the dairy industry. This study attempts to develop an alternative strategy to convert the dairy wastewater into liquid biofertilizer. A tailor-made microbial consortium-based biofilm reactor with 8.64 m 3 d −1 processing capacity, within 16 h of hydraulic retention time (HRT) at ambient temperature produced biofertilizer containing 96.01 mg L −1 ammonia from dairy wastewater at a flow rate of 360 L h −1 with associated 73.72% nitrate, 72.46% phosphate, 61.30% Biological Oxygen Demand (BOD) and 57.23% Chemical Oxygen Demand (COD) reduction. A similar system of 10.94 m 3 d −1 processing capacity at 456 L h −1 flow rate produced 298.79 mg L −1 ammonia with nitrate, phosphate, BOD and COD reduction of 42.71%, 84.80%, 89.55% and 76.68% respectively. This liquid biofertilizer could enhance grain yield in maize ( Zea mays var. Vijay) by 1.19-fold. It increased biomass yield in Sorghum Sudan grass ( Sorghum sudanense ) by 3.5-folds and Lemongrass ( Cymbopogon citratus var. Dhanitri and var. Krishna) by 2.1 and 2.64 folds respectively. It enhanced gel content in Aloe vera ( Aloe elongata var. Ghikuari) by 1.63-folds when compared to chemical fertilizer treatment. This single-step dairy wastewater treatment system requires ten times less energy with the development of a value-added product (biofertilizer). It could make the dairy wastewater management a revenue earning (USD 10.28 d −1 for 600 m 3 d −1 processing capacity reactor), eco-friendly, zero discharge process preventing the use of freshwater and chemical fertilizer in agriculture, and saving 89.99% carbon dioxide equivalent (CO2 eq.) gas emission leading to environmental protection. Graphical abstract: Image 1 Highlights: Single-step process compared to 7–8 steps necessary in conventional wastewater treatment. Microbe based bioconversion of dairy wastewater to ammonia rich biofertilizer. Liquid biofertilizer enhanced yield of economic crop compared to chemical fertilizer. 2.5 times inexpensive, 10 times less energy intensive compared to conventional system. Minimizes fresh water consumption, 89.99% savings on CO2 equivalent gas emission.